2021
DOI: 10.1038/s41598-021-91452-4
|View full text |Cite
|
Sign up to set email alerts
|

Host specific endophytic microbiome diversity and associated functions in three varieties of scented black rice are dependent on growth stage

Abstract: The compositional and functional role of the endophytic bacterial community, associated with black scented rice, in correlation with its antioxidant property has been elucidated. Community dissimilarity analysis confirmed the overlapping of community in shoot and root tissues at the young stage, but not in mature plants. Proteobacteria was the most abundant phylum, in which Agrobacterium, Pleomorphomonas, Bradyrhizobium, Novasphingobium, Caulobacter were the most abundant genera, followed by Cyanobacteria and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(25 citation statements)
references
References 61 publications
3
19
0
Order By: Relevance
“…The main bacterial phyla in the three different organs of ginseng were Proteobacteria, Bacteroidetes, and Actinobacteria. The relative abundance of these species varied between the different organs of ginseng, which is consistent with the results of most studies (Singha et al 2021;Hong et al 2018;Gouda et al 2016). Previous studies have shown that Actinobacteria, and Proteobacteria were common phyla in plant tissues, they play a key role in participating in host metabolism and maintaining the stability of the endophytic micro ora (Bashir et al 2020;Müller et al 2015).…”
Section: Discussionsupporting
confidence: 88%
“…The main bacterial phyla in the three different organs of ginseng were Proteobacteria, Bacteroidetes, and Actinobacteria. The relative abundance of these species varied between the different organs of ginseng, which is consistent with the results of most studies (Singha et al 2021;Hong et al 2018;Gouda et al 2016). Previous studies have shown that Actinobacteria, and Proteobacteria were common phyla in plant tissues, they play a key role in participating in host metabolism and maintaining the stability of the endophytic micro ora (Bashir et al 2020;Müller et al 2015).…”
Section: Discussionsupporting
confidence: 88%
“…In dual receptor recognition, the exchange of signals combined with plant and microbial genetic potential helps to determine the ultimate fate of the interaction [ 23 ]. Finally, although microbes in the soil exist in the presence of a large number of other microbes, plants have to integrate their nutritional status with their expression of immunity to maintain homeostasis [ 21 , 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Host facthat, as already observed for legume plants tors such as genotype and host phylogenetic relationships play a role in shaping endophytic communities of rice cultivars. Furthermore, it is increasingly evident that environmental conditions such as soil nutrition, moisture, and temperature have a direct influence on endophere communities [ 64 ]. O. glaberrima and O. sativa have adapted to growth in very different climatic conditions: O. glaberrima is adapted to harsh African climate and presents resistance or tolerance to viruses, nematode, bacteria, drought, iron toxicity and high salinity [ 65 , 66 ], while O. sativa cv.…”
Section: Discussionmentioning
confidence: 99%